REFORMULATING VILLAGE HEAD AUTHORITY IN ISSUING HEIR CERTIFICATES: SURABAYA CASE UNDER PUBLIC SERVICES LAW - Jussaq Noor Hamdhani (IUS POSITUM: Journal of Law Theory and Law Enforcement, 2025)
The Regulation of the Minister of Agrarian Affairs and Head of the National Land Agency Number 3 of 1997 concerning Land Registration explains that residents of native Indonesian descent can obtain Heir Certificates at the village office witnessed by the sub-district head, village head, and two witnesses. However, this regulation does not clearly specify the scope of village head authority and the technical procedures for issuing Heir Certificates. These unclear boundaries create legal uncertainty and concern among village heads regarding legal protection in carrying out their duties, including in Surabaya City. Therefore, the Surabaya City Government periodically reformulates articles in the Mayor's Regulations to improve village office performance as the frontline of public services, particularly in issuing Heir Certificates. This normative juridical research employs statutory and conceptual approaches. The findings indicate that regulations governing village head authority in issuing Heir Certificates have implemented most principles of public service outlined in Law Number 25 of 2009 concerning Public Services. To enhance village service performance, reformulation is needed to fulfill several principles including legal certainty, equal rights, professionalism, participation, equal treatment or non-discrimination, accountability, facilities and special treatment for vulnerable groups, timeliness, speed, convenience, and affordability.